An analysis of event tourism in Malaysia - Norazirah, Ayob (Centre for Research on Tourism, 2003)
Event tourism is becoming popular in Malaysia. Hence, it can be viewed as a significant segment of the Malaysian tourism industry. Yet, there are no adequate data that can help analyse and understand the development of the event tourism sector for further tourism destination planning and marketing. Basically, each festival and special event has its own role and purpose to play. Traditionally celebrated by local communities as rituals of traditions, beliefs and religion, the events are now being used and marketed as tourism attractions. There were certain trends that can be observed from 1990 until 2000. The Malaysian event tourism is analysed according to certain episodes that happened since then. Essentially, the event tourism sector in Malaysia is going through a considerable growth in numbers, size and attendance, diversity, and professionalism.